The catcher in the rye innocence under pressure - Pinsker, Sanford (Twayne's masterwork studies, 1993)
Sanford Pinsker's reading of the Catcher in the Rye goes through the novel chronologically, in a manner perfectly conducive to side-by-side reading, and provides helpful chapters on historical background and critical reception.